Comparative study on the performance of Au/F-TiO2 photocatalyst synthesized from Zamzam water and distilled water under blue light irradiation - Zayadi, R.A.; Abu Bakar, F. (Elsevier Science Ltd, 2017)
Recurring problems of titanium dioxide (TiO2) for needing UV light to be activated and high electron-hole recombination rate limit the application of TiO2 as a proliﬁc photocatalyst. By modifying the morphology and introducing electron trapping species into TiO2, the photocatalytic activity of TiO2 could be improved. Solvents of two different kinds; distilled water and Zamzam water were used in peroxotitanic acid synthesis of TiO2 and the photocatalyst was utilized to degrade Reactive Blue 19 (RB19) dye under blue light irradiation (475 nm) to assess the visible light activity of synthesized TiO2. Fluorine was incorporated to control the morphology while gold nanoparticles (GNP) stabilized by arabic gum were deposited to trap electrons. The morphology of F-TiO2 which appeared to be in ovoid shape was conﬁrmed by Field Emission-Scanning Electron Microscope (FE-SEM) and Transmission Electron Microscope (TEM). Brunauer-Emmett-Teller (BET) surface area and crystallite size estimated from X-ray Diffraction (XRD) data revealed that F-TiO2 modiﬁed using HF was smaller in size and exhibited single anatase phase. The band gap of Au-TiO2 synthesized by distilled and Zamzam water was 2.78 eV and 2.89 eV respectively; shifted from 3.08 eV in blank TiO2. Peroxo Au/F-TiO2 synthesized with the incorporation of arabic gum as GNP stabilizer and HF as ﬂuorine modiﬁer degraded up to 49.23% of RB19 within two hours of reaction. The addition of ﬂuorine and gold demonstrated high ability to enhance visible light activity of TiO2 with distilled water used as solvent displayed higher photocatalytic performance compared to Zamzam water.